Między słowem a obrazem. Z notatnika reżysera - Gliński, Robert (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2011)
Between script and film camera For the film director the film is, in a way, “ready” before the shooting. Everything what is important for the film must be planned and worked out before its shooting. The interval between writing the script and the shooting the film is the intensive time of work for the director. He/she must decide what (kind of) movie he/she wants to do. The director must know how to organize the scenes for the shots, how the film should start and end. He/she must know who will play in the film and find a way to inspire the actors. The director prepares the rehearsals. He/she is also supposed to find interiors and exteriors for shooting, write the screenplay and draw the storyboard. The satisfy all these requirements of director has to be not only talented but work hard, be concentrated and persistent. Effects of his/her devotion to film are revealed in how the text of the script is turned into film.